2015
DOI: 10.1016/j.scr.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Inducible expression of noggin selectively expands neural progenitors in the adult SVZ

Abstract: Multipotent, self-renewing stem cells are present throughout the developing nervous system remaining in discrete regions of the adult brain. In the subventricular zone (SVZ) signaling molecules, including the bone morphogenetic proteins and their secreted inhibitor, noggin appear to play a critical role in controlling neural stem cell (NSC) behavior. To examine the function of this signaling pathway in the intact nervous system, we developed a transgenic mouse model in which noggin expression can be induced sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…BMP receptor activation inhibits proliferation and suppresses SVZ neurogenesis while promoting gliogenesis (Lim et al, ). Several groups have further shown that BMP suppresses oligodendrogenesis while promoting astrogenesis (Gomes, Mehler, & Kessler, ; Mabie et al, ; Morell, Tsan, & O'Shea, ). Other data suggest BMP suppresses the oligodendrocytic fate but has a permissive effect on olfactory bulb neurogenesis (Colak et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP receptor activation inhibits proliferation and suppresses SVZ neurogenesis while promoting gliogenesis (Lim et al, ). Several groups have further shown that BMP suppresses oligodendrogenesis while promoting astrogenesis (Gomes, Mehler, & Kessler, ; Mabie et al, ; Morell, Tsan, & O'Shea, ). Other data suggest BMP suppresses the oligodendrocytic fate but has a permissive effect on olfactory bulb neurogenesis (Colak et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…BMP receptor activation inhibits proliferation and suppresses SVZ neurogenesis while promoting gliogenesis (Lim et al, 2000). Several groups have further shown that BMP suppresses oligodendrogenesis while promoting astrogenesis (Gomes, Mehler, & Kessler, 2003;Mabie et al, 1997;Morell, Tsan, & O'Shea, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used approaches to induce differentiation of MSCs into neuron-like cell include (1) antioxidant agents such as mercaptoethanol, dimethylsulfoxide (DMSO), and beta hydroxy acid (BHA); (2) neurotropic factors such as retinoic acid (RA), nerve growth factor (NGF), epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), brain derived neurotropic factor (BDNF); (3) Chinese herbs and their effective components such as astragalus glycosides, berberine, tanshinone, lycium barbarum polysaccharide, acanthopanax; (4) cultural method; and (5) gene transfection: transfection of specific genes such as Noggin [5] and Notch into hUC-MSCs to get neuron-like cell. However, these differentiation approaches are of low efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focused on bone morphogenetic proteins (BMPs). BMPs are expressed locally within the SVZ, where they have been shown to promote production of astrocytes at the expense of neurons and oligodendrocytes (Lim et al, 2000 ; Morell et al, 2014 ). Inhibition of endogenous BMP signaling modulates neurogenesis in both the SVZ and dentate gyrus niches, although there is conflicting data that likely reflects unresolved stage-specific effects on the neurogenic lineage and differences between niches (Lim et al, 2000 ; Bonaguidi et al, 2008 ; Colak et al, 2008 ; Gobeske et al, 2009 ; Mira et al, 2010 ; Guo et al, 2011 ; Bond et al, 2012 , 2014 ).…”
Section: Introductionmentioning
confidence: 99%